Проблеми кваліфікації кримінальних правопорушень, передбачених статтями 342 та 345 КК України - Орлов, Ю. В.; Orlov, Yu. V.; Щебетун, С. В.; Shchebetun, S. V.; Орлов Юрій Володимирович (Вісник Кримінологічної асоціації України. - 2025. - № 2 (35). - С. 25-45, 2025)
Статтю присвячено дослідженню проблем кваліфікації кримінальних правопорушень, передбачених ст. ст. 342 та 345 КК України, при відмежуванні від інших правопорушень, а також при розмежуванні один з одним. Встановлено, що основним об’єктивно-атрибутивним критерієм відмежування злісної непокори (ст. 185 КУпАП) від опору (ст. 342 КК України) є фізичне спрямування дій особи. Агресивні, такі, що свідчать про напад, рухи у бік працівника правоохоронного органу однозначно свідчать про опір. Рухи від працівника правоохоронного органу, що мають характер захисту від активних дій останнього, слід кваліфікувати як злісну непокору. Виділено та охарактеризовано специфічні ситуації службової діяльності поліцейських, в яких проявляється злісна непокора та/або опір. Визначено, надано опис та пояснення розмежувальним ознакам складів кримінальних правопорушень, передбачених ст. ст. 342 та 345 КК України.

The article is devoted to the study of the problems of qualification of criminal offenses provided for by Articles 342 and 345 of the Criminal Code of Ukraine, when distinguishing them from other offenses, as well as when distinguishing them from each other. It has been established that the main objective and attributive criterion for distinguishing malicious disobedience (Article 185 of the Code of Administrative Offenses) from resistance (Article 342 of the Criminal Code of Ukraine) is the physical direction of the person. Aggressive, such as those indicating an attack, movements towards a law enforcement officer clearly indicate resistance. Movements from a law enforcement officer that are of a protective nature against the latter’s active actions should be qualified as malicious disobedience. Specific situations of police officers' official activities in which malicious disobedience and/or resistance are manifested are highlighted and characterized. The distinguishing features of the elements of criminal offenses provided for in Articles 342 and 345 of the Criminal Code of Ukraine are defined, described and explained.
Problems of qualification of criminal offences provided for by Articles 342 and 345 of the Criminal Court of Ukraine
Keywords: правоохоронні органи; авторитет; службові повноваження; злісна непокора; опір; погроза; насильство; масові заходи; тактика; тілесні ушкодження; життя; здоров’я; склад кримінального правопорушення; кримінальна відповідальність; кваліфікація; law enforcement agencies; authority; official powers; malicious disobedience; resistance; threat; violence; mass events; tactics; bodily harm; life; health; elements of a criminal offense; criminal liability; qualification